Enriching and quantifying porous single layer 2D polymers by exfoliation of chemically modified van der Waals crystals - Lange, Ralph Z.; Synnatschke, Kevin; Qi, Haoyuan; Huber, Niklas; Hofer, Gregor; Liang, Baokun; Huck, Christian; Pucci, Annemarie; Kaiser, Ute; Backes, Claudia; Schlüter, A. Dieter (Angewandte Chemie. International edition, 2020)
2D polymer sheets with six positively charged pyrylium groups at each pore edge in a stacked single crystal can be transformed into a 2D polymer with six pyridines per pore by exposure to gaseous ammonia. This reaction furnishes still a crystalline material with tunable protonation degree at regular nano-sized pores promising as separation membrane. The exfoliation is compared for both 2D polymers with the latter being superior. Its liquid phase exfoliation yields nanosheet dispersions, which can be size-selected using centrifugation cascades. Monolayer contents of ≈30 % are achieved with ≈130 nm sized sheets in mg quantities, corresponding to tens of trillions of monolayers. Quantification of nanosheet sizes, layer number and mass shows that this exfoliation is comparable to graphite. Thus, we expect that recent advances in exfoliation of graphite or inorganic crystals (e.g. scale-up, printing etc.) can be directly applied to this 2D polymer as well as to covalent organic frameworks.
First published: 10 December 2019
Gesehen am 23.04.2020